2016
DOI: 10.1177/2168479015600205
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Premium Rewards for the Promotion of Innovative Drug Discovery on the Japanese Pharmaceutical Market: An Analysis by Therapeutic Area

Abstract: Our study suggests that this system has been working according to its original aim of promoting the development of innovative drugs in Japan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 19 publications
(22 reference statements)
0
19
0
Order By: Relevance
“…In addition, we reported that the reward system unique to Japan has had a positive effect on drug sales in specific therapeutic areas, such as N and L drugs, indicating that the government has encouraging the development of these drugs. 20 The R 2 values for France and Germany suggest that these markets are also transitioning to a global market, and that they are currently at a more advanced stage than Japan (Figure 3). However, it is notable that the United Kingdom, Germany, and France, which have less market share than Japan (Table 1), are closer to a global market.…”
Section: Discussionmentioning
confidence: 96%
“…In addition, we reported that the reward system unique to Japan has had a positive effect on drug sales in specific therapeutic areas, such as N and L drugs, indicating that the government has encouraging the development of these drugs. 20 The R 2 values for France and Germany suggest that these markets are also transitioning to a global market, and that they are currently at a more advanced stage than Japan (Figure 3). However, it is notable that the United Kingdom, Germany, and France, which have less market share than Japan (Table 1), are closer to a global market.…”
Section: Discussionmentioning
confidence: 96%
“…The ''NHI Drug Price Premium for Promoting the Creation of New Drugs and the Elimination of Offlabel Use'' is a price addition within the Japanese NHI drug pricing system. [19][20][21] This price addition is targeted at medicines whose price divergence rates (ratio of delivery price to official price) are lower than average (across all medicines). The medicines for which such a price addition are received are targeted for a special price reduction by the government in the drug price revision after the first generic medicine enters the market.…”
Section: Analysis Of Sales After Generic Entrymentioning
confidence: 99%
“…The share of cardiovascular system drugs is relatively high among the top 100 drugs in the Japanese market, while that of antineoplastic and immunomodulating agents is relatively low. 3 Because the Japanese drug pricing system has encouraged R&D of new antineoplastic and immunomodulating agents and nervous system drugs that are likely to sell well in the Western market as well as the Japanese market, [4][5][6] the Japanese pharmaceutical market for these drugs is regarded as becoming similar to the markets of Western countries. 2 However, because the research focus on new molecular entities (NMEs) in Japan is limited, it is essential to discuss the prognosis of the Japanese pharmaceutical market.…”
Section: Introductionmentioning
confidence: 99%